PENGARUH EFISIENSI BIAYA BAHAN BAKU, BIAYA TENAGA KERJA LANGSUNG DAN BIAYA OVERHEAD PABRIK TERHADAP PROFIT MARGIN PADA CV. INDOSCOTS BABY UTAMA PALEMBANG - Rizal Effendi; Deta Astra Putri (Jurnal RATRI (Riset Akuntansi Tridinanti), 2019)
ABSTRACK                This research was conducted aimed to determine and analyze the effect of the efficiency of production costs consisting of the efficiency of raw material costs, efficiency of direct labor costs, efficiency of factory overhead costs to provit margins on the CV. Main Baby Indoscots. The research period began from January 2014 to June 2016. Simultaneous hypothesis testing (statistical test F) and partially (statistical test t) with α = 5%. The management of the researcher data is assisted by using SPSS version 18.00. Significant F (simultaneous) test results Fcount> Ftable (5.568> 2.96) address the variable version of production costs consisting of the efficiency of raw material costs, the efficiency of direct labor costs, and the efficiency of factory overhead costs together positively and significantly impact on profits margin. The results of the t test (partial) showed that the efficiency of the cost of raw materials was significant tcount> ttable (1,895> 1,706), the efficiency of direct labor costs was significant tcount> ttable (1,919> 1,706), the efficiency of factory overhead was significant tcount <ttable (-1,354 <1,706) ), significantly influences profit margin.Keywords: Cost Efficiency of Raw Materials, Efficiency of direct wages, Factory Overhead Cost Efficiency.